A pilot study of the effect of a home‐based multimodal symptom‐management program in children and adolescents undergoing chemotherapy. Issue 3 (15th February 2021) - Cheng, Karis Kin‐Fong; Tan, Laura Mei Lian
Abstract: Background: Prevalent symptoms that affect children and adolescents throughout the process of cancer diagnosis and treatment include nausea and vomiting, fatigue, pain, mucositis, and anxiety. Aim: To examine the effect of a home‐based multimodal symptom‐management program for alleviation of nausea and vomiting, fatigue, pain, mucositis, and anxiety in children and adolescents undergoing chemotherapy for hematological malignancies or solid tumors. Methods: In an exploratory pilot randomized study with qualitative interview, patients between 10 and 18 years of age were randomly assigned to either the symptom‐management program plus usual care (intervention group) or usual care (control group). The program consisted of multiple nonpharmacological interventional components. The targeted symptoms were measured at baseline (after diagnosis), at the first 2 weeks of each cycle of chemotherapy, and at 6 months after baseline, using the Memorial Symptom Assessment Scale 10‐18 and the State Anxiety Scale for Children. Results: Fifty children (31 boys; mean age, 13.7 years) were randomized either to the intervention group or the control group (25 each) and underwent baseline assessment. A comparison between the groups showed that the intervention group had a significant less fatigue over time ( P  < .05). However, no differences were found with respect to nausea and vomiting, pain, mucositis, and anxiety between groups. Both children and parents reported a positive experience with the symptom‐management program. Conclusion: The home‐based symptom‐management program may have helped to reduce fatigue in children and adolescents undergoing chemotherapy. In addition, qualitative data support the importance of improving children and parents' knowledge, coping skills, and psychological preparation for symptoms associated with chemotherapy.